Effectiveness of alectinib and osimertinib in a brain metastasized lung adenocarcinoma patient with concurrent EGFR mutations and DCTN1‐ALK fusion. Issue 4 (28th December 2021) - Yin, Qiang; Guo, Taiyan; Zhou, Yangyang; Sun, Leina; Meng, Maobin; Ma, Li; Wang, Xiaoguang
Abstract: The echinoderm microtubule associated protein‐like 4 gene ( EML4 ) encodes the predominant anaplastic lymphoma kinase ( ALK ) fusion partner in non‐small‐cell lung cancer (NSCLC); however, the dynactin subunit 1 ( DCTN1 )‐ ALK rearrangement is extremely rare. The co‐occurrence of primary epidermal growth factor receptor (EGFR) T790M mutation with EGFR exon 19 deletion (del) in patients with NSCLC is uncommon. Here we report a female lung adenocarcinoma patient with brain metastases and possible coexistence of primary EGFR T790M mutation/ EGFR exon 19 del/ DCTN1‐ALK translocation. The patient received multiline treatment including chemotherapy, antivascular, and targeted therapies. To overcome developed resistance to chemotherapy or targeted therapy to prolong overall survival, the patient's circulating tumor DNA (ctDNA) was dynamically monitored. The patient responded to successive osimertinib and alectinib treatment, and alectinib achieved a nearly complete response for lung and brain lesions after she acquired osimertinib resistance. Furthermore, we summarize 22 published cases of patients with lung adenocarcinoma with concurrent EGFR mutation and ALK rearrangement, including details of clinical characteristics, natural history, and pertinent therapy of this uncommon tumor subtype. This literature review shows that EGFR inhibition was an indispensable aspect of the treatment of patients with EGFR/AL K co‐alterations in the pre‐alectinib era and that ALK inhibition with crizotinib did not show more eye‐catching therapeutic results. Considering the effectiveness achieved by alectinib, this case study provides a new perspective for the treatment of lung cancer brain metastasis patients with concurrent EGFR/ALK mutations. Abstract : We report a female lung adenocarcinoma patient (T3N2M1a) with brain metastases and possible coexistence of primary EGFR T790M mutation/EGFR exon 19 del/DCTN1‐ALK translocation. The patient was sensitive to multiple treatment, including initial chemotherapy as well as the later administration of apatinib, osimertinib, and alectinib. We also summarize 22 published cases of lung adenocarcinoma patients with concurrent EGFR mutation and ALK rearrangement.